2008
DOI: 10.1093/hmg/ddn352
|View full text |Cite
|
Sign up to set email alerts
|

MCP-1 promoter variant -362C associated with protection from pulmonary tuberculosis in Ghana, West Africa

Abstract: Current endeavour focuses on human genetic factors that contribute to susceptibility to or protection from tuberculosis (TB). Monocytes are crucial in containing Mycobacterium tuberculosis infection, and the monocyte chemoattractant protein-1 (MCP-1) cytokine plays a role in their recruitment to the site of infection. The G allele of the MCP-1 promoter polymorphism at position -2581 relative to the ATG transcription start codon has been described to be associated in Mexican and Korean TB patients with increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
5
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 15 publications
(21 reference statements)
2
72
5
1
Order By: Relevance
“…The results of the study are consistent with those of previous reports regarding the association between MCP-1 -2518A/G polymorphisms and tuberculosis in Mexicans, Koreans, Peruvians, Tunisians, and Zambians (Flores-Villanueva et al, 2005;Buijtels et al, 2008;Ganachari et al, 2010;Ben-Selma et al, 2011). Others have reported different results, such as in South African Coloreds, Indians, and Ghanaians (Alagarasu et al, 2009;Moller et al, 2009;Thye et al, 2009). Different genetic backgrounds may account for these differences.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the study are consistent with those of previous reports regarding the association between MCP-1 -2518A/G polymorphisms and tuberculosis in Mexicans, Koreans, Peruvians, Tunisians, and Zambians (Flores-Villanueva et al, 2005;Buijtels et al, 2008;Ganachari et al, 2010;Ben-Selma et al, 2011). Others have reported different results, such as in South African Coloreds, Indians, and Ghanaians (Alagarasu et al, 2009;Moller et al, 2009;Thye et al, 2009). Different genetic backgrounds may account for these differences.…”
Section: Discussionsupporting
confidence: 91%
“…Pathogen variation may underlie some of the difficulties in finding loci for a given infectious disease and M. tuberculosis displays substantial geographic variation in genotype frequencies 9 . However, as we have shown previously and also here [9][10][11][12][13] , combined analyses with increased aggregate sample sizes may help in the identification of novel genetic variants, perhaps particularly those less sensitive to pathogen variation. Analyzing African individuals poses specific challenges, and genetic differences between populations, even within West Africa, are large enough to complicate standard imputation procedures.…”
Section: Introductionsupporting
confidence: 60%
“…Discrepant results obtained from genotypeand allele-based TB association studies with MCP-1 variants (especially at Ϫ2518) ( Table 1) failed to yield solid evidence for genetic effects of MCP-1. Carriers of the Ϫ2518 GG genotype were reported to produce high levels of MCP-1, which inhibits IL-12 production in response to M. tuberculosis and promotes active pulmonary TB (78), whereas Thye et al (227) initially found association of the Ϫ2518G allele with TB resistance in Ghana, and further genotyping led to the identification of the Ϫ362C allele as the putatively "true" protective variant of MCP-1, reflecting linkage disequilibrium between Ϫ2518 and Ϫ362. This study is a cautionary note for the need to carry out a thorough genetic investigation to search for the actual causative polymorphism.…”
Section: Mcp-1 (Ccl2)mentioning
confidence: 99%